2016
DOI: 10.1057/palcomms.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Independence of events, and errors in understanding it

Abstract: This article outlines errors that may occur when people predict event outcomes. The focus is on how our tendency to perceive independent events as connected, consistent with tenets of Gestalt Psychology, biases our expectations. Two well-documented phenomena that occur when people make predictions after a run of a particular outcomethe "gambler's fallacy" and the "hot hand"-are used to illustrate the issue, and research is presented that highlights the importance of misperceptions of independence. Novel implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The study confirmed students' problems with understanding the concept of independence as known from the literature (Díaz et al, 2010;Roney, 2016). In the tasks on independence (1-6), to an extent, the students could create sample spaces for two-stage experiments, which indicates that their probabilistic thinking is on the unistructural level (Mooney et al, 2014).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The study confirmed students' problems with understanding the concept of independence as known from the literature (Díaz et al, 2010;Roney, 2016). In the tasks on independence (1-6), to an extent, the students could create sample spaces for two-stage experiments, which indicates that their probabilistic thinking is on the unistructural level (Mooney et al, 2014).…”
Section: Discussionsupporting
confidence: 67%
“…Two well-documented misconceptions in this area are the gambler's fallacy and the hot hand fallacy (Roney, 2016), in which the law of large numbers plays a crucial role. It posits that the ratio of the outcomes corresponding to event A and all the outcomes approaches the probability of event A.…”
Section: Students' Perception Of Independencementioning
confidence: 99%
See 3 more Smart Citations